Heterogeneous Technology Diffusion and Ricardian Trade Patterns - William R. Kerr (Center for Economic Studies and ifo Institute (CESifo), 2016)
Migration and trade are often linked through ethnic networks boosting bilateral trade. This study uses migration to quantify the importance of Ricardian technology differences for international trade. The framework provides the first panel estimates connecting country-industry productivity and exports, and the study exploits heterogeneous technology diffusion from immigrant communities in the United States for identification. The latter instruments are developed by combining panel variation on the development of new technologies across U.S. cities with historical settlement patterns for migrants from countries. The instrumented elasticity of export growth on the intensive margin with respect to the exporter's productivity growth is between 1.6 and 2.4 depending upon weighting. This provides an important contribution to the trade literature of Ricardian advantages, and it establishes a connection of migration to home country exports beyond bilateral networks.
Keywords: F11; F14; F15; F22; J44; J61; L14; O31; O33; O57; 330; trade; exports; comparative advantage; technological transfer; patents; innovation; research and development; immigration; networks